Keanekaragaman Tumbuhan Pakan Bagi Tapir (Tapirus indicus), Kijang (Muntiacus muncak), Kukang (Nycticebus coucang) dan Kondisi Habitat di Kawasan Gunung Tujuh, Taman Nasional Kerinci Seblat, Jambi - W. Rosa Farida; Wirdateti Wirdateti; H. Dahruddin; G. Sumaatmadja (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
A study on the diversity of feed plants of tapir (Tapirus indicus), barking deer (Muntiacus muncak), and slow loris (Nycticebus coucang) as well as their habitat condition has been conducted at Gunung Tujuh, Kerinci Seblat National Park, Jambi. Survey was carried out by visiting places where the animals are usually found and by taking collection of herbarium plant specimens of those animals’ feed. The habitat of tapir is in a region of Gunung Tujuh forest up to the altitude of 2,020 m above sea level, while that of barking deer is in Gunung Tujuh forest where dense bushes at the edges of forest until the altitude of 1620 m above sea level is favored and that of slow loris is in low region of forest. Thirty eight species belonging to 25 families of forest plants as feed resources for tapir, barking deer, and slow loris were found. Amaranthaceae, Anonaceae, Clusiaceae, Moraceae, and Myrsinaceae were recorded as feed plants for tapir, while Euphorbiacea, Fagacea, Lauracea, and Urticacea were for slow loris and Solanaceae was for barking deer.